Phytochemical composition and antibacterial potential of Melastoma malabathricum against Staphylococcus aureus with in silico insights into MRSA target proteins - FEBRIA ELVY SUSANTI; MAI EFDI; SYAFRIZAYANTI SYAFRIZAYANTI; ABDI WIRA SEPTAMA; NURYANI TURABBY (Society for Indonesian Biodiversity, 2025)
Abstract. Susanti FE, Efdi M, Syafrizayanti, Septama AW, Turabby N. 2025. Phytochemical composition and antibacterial potential of Melastoma malabathricum against Staphylococcus aureus with in silico insights into MRSA target proteins. Biodiversitas 26: 6000-6013. The global rise in antimicrobial resistance highlights the need to explore new antibacterial agents derived from natural sources. Melastoma malabathricum, a medicinal plant rich in phenolic compounds, was investigated for its antioxidant and antibacterial properties, with additional in silico analysis of potential interactions with MRSA-related target proteins. Methanol extracts from different plant parts (leaves, stems, fruits, roots, and flowers) were evaluated for their Total Phenolic Content (TPC), antioxidant activity, and antibacterial effects against methicillin-sensitive Staphylococcus aureus (MSSA, ATCC 29213) and Escherichia coli (ATCC 25922). The flower extract showed the widest inhibition zone of 14.17 mm against S. aureus ATCC 29213 (MSSA), and the highest IC50 value (89.22 mg/L) was obtained from the root extract, indicating the lowest antioxidant activity. The TPC of the extracts reached 140.84 mg GAE/g. Molecular docking revealed that afzelin, quercetin, and trifolin may bind to MRSA-associated proteins, including PBP2a, DdlB, and FabH, suggesting possible mechanisms underlying the observed antibacterial effects. These findings imply that phenolic compounds in M. malabathricum could act through multiple molecular targets, contributing to its biological activities. However, since the antibacterial assays were conducted using a methicillin-sensitive strain, further validation using MRSA isolates is required to confirm the predicted inhibitory potential. Overall, this study provides a preliminary understanding of the phenolic composition and antibacterial potential of M. malabathricum, supporting its continued investigation as a natural source of bioactive compounds.